Pengaruh Kepemimpinan Kepala Sekolah dan Motivasi Kerja terhadap Kinerja Guru di Yayasan Pendidikan Charitas - Markus Wilmar Fau; Sarmini Sarmini; Siti Aisyah (Universitas Kristen Satya Wacana, 2022)
This study is intended to analyze the effect of leadership style and work motivation on teacher performance at the Charitas educational foundation. The variables studied were leadership style (X1), work motivation (X2), and performance (Y). The method used in this research is a quantitative approach with a correlational design. Sampling using stratified random sampling as many as 53 respondents. Data collection techniques using questionnaires, interviews, and documentation. The analysis technique uses descriptive statistics, and inferential statistics with multiple linear regression. From the results of multiple regression analysis, the performance equation (Y) = 35.003 – 0.060X1 + 0.674X2 +. From the results of multiple regression analysis, it can be seen that the work motivation variable has a greater value in influencing employee performance. From the results of the F test, Fcount > Ftable is 15.492 > 2.77. It can be concluded that the variables of leadership style, and work motivation, simultaneously and significantly affect the performance of teachers at the Charitas Education Foundation. From the results of the t test, it can be concluded that the work motivation variable has a significant effect on performance with a significant level of 0.05, while leadership style has no effect on performance. The results of the analysis of the coefficient of determination of 0.362 or 36.2% of the leadership style variable, and work motivation can explain the variation of the performance variable, while the remaining 63.8% is explained by other variables outside of this study.